PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PERSONIL DIREKTORAT KRIMINAL KHUSUS KEPOLISIAN DAERAH SUMATERA SELATAN - Try Nensy Nirmalasary; Fakhry Zamzam; Luis Marnisah (MAP Program Pascasarjana Universitas Sjakhyakirti, 2020)
Job satisfaction and work motivation are directly related to personnel performance. Job satisfaction and work motivation felt by personnel can reduce performance or increase personnel performance. personnel who are satisfied with the work obtained will be motivated to improve performance so that it will have an impact on increasing overall organizational performance. This research was conducted at the Directorate of Special Criminal Investigation at the South Sumatra Regional Police, which aims to analyze how motivation and job satisfaction influence the performance of the Police Personnel at the Special Criminal Research Directorate for the South Sumatra Regional Police. The applied research model is a survey method, using 82 samples from a population of 92 Polri personnel at the Special Criminal Investigation Directorate for the South Sumatra Regional Police, using multiple regression analysis. The data analysis technique uses descriptive statistics and inferential statistics. In this study, the types of data used are primary data and secondary data. The data collection techniques used questionnaires, interviews, observation and documentation. Hypothesis testing through t test and F test using SPSS analysis tools. The results of data processing using SPSS 25, using the t test that t count is 4.021> with t table 1.993 and a significance level of 0.025 <0.05 that there is a positive and significant influence on motivation on performance; that t count is 3.025> with t table 1.993 and a significance level of 0.041 <0.05 that there is a positive and significant effect of job satisfaction on performance; and using the F test that F counts at 7,194> with F table 2.683 and a significance level of 0.00 <0.05 that there is a positive and significant effect on the pattern of motivation and job satisfaction together on performance, with a coefficient of determination of 49.3% the rest is influenced by other variables. The results showed that motivation and job satisfaction have a positive and significant effect on performance either partially or simultaneously. The career development strategy of the Police Personnel of the Directorate of Special Criminal Investigation at the South Sumatra Regional Police is very much determined by providing remuneration received by personnel on time according to applicable regulations, then increasing the work motivation of personnel with leadership techniques always giving appreciation for personnel work performance.